Smartphone induced eye strain in young and healthy individuals - Nayak, Rakhi; Sharma, Ananda Kumar; Mishra, Sanjeeb Kumar; Bhattarai, Sanjeev; Sah, Nirajan Kumar; Sanyam, Sandip Das (Journal of Kathmandu Medical College, 2020)
Background: Usage of digital devices has become one's basic need. Digital eye strain is repeatedly noticed sequelae in optometry practice.Objectives: This study aims to estimate the different aspects of eye strain.Methodology: Altogether, 55 students with a mean age of 21.25 years, vision (≥6/9) were enrolled. A survey related to common asthenopic (eyestrain) symptoms was carried before and after reading an extract from a novel. Accommodative facility and non-invasive first tear breakup (NTBUT) time were measured before and after the reading. The viewing distance to a smartphone was measured every 20 minute.Results: The total eye strain symptom score was significantly greater post-experiment (score = 7.07±2.84) than pre-experiment (score = 1.54±1.60, p < 0.001). Symptoms of tired eyes, sore eyes, and sleepy eyes increased significantly after 60 min of a smartphone use (p < 0.05). The mean viewing distance while using a smartphone over 60 min was 30.15 ± 3.29 cm.  There was a significant correlation between change in total symptom score and change in viewing distance (r = ˗0.301, p = 0.026). The symptom that correlated with a change in viewing distance was ‘sore eyes’ (r = ˗0.382, p = 0.04) and sleepy eyes (r= ˗0.363, p=0.06). There was a significant decrease in monocular and binocular accommodative facilities and NTBUT after 60 min of reading.Conclusion: Closer viewing distance and eyestrain symptoms are obvious after a smartphone reading. Prolonged use of smartphones appears to have important implications for accommodative function, causing ocular symptoms having an impact on quality of life.